Pemanfaatan Sampah Plastik untuk Produksi Eco-Bricks sebagai Hiasan Kebun Mini di Desa Teluk Sasah - Ramadhany Saputra; Randika Achmadi; Ikram Masbullah; Eka Widiarti; Ayu Wandira; Junitasari Junitasari; Yunita Aisah Triyani; Ibaniyah Ibaniyah; Hanisa Hanisa; Dina Fitriyah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Ecobricking is an innovative approach to waste management that involves processing inorganic waste, particularly plastics, into durable ecobrick products. This practice has been successfully implemented in Desa Teluk Sasah, Seri Kuala Lobam District, Bintan Regency, by the KKN 40 Desa Teluk Sasah team from Maritim Raja Ali Haji University in 2025. Plastic waste continues to dominate the waste stream in coastal areas and surrounding regions of Desa Teluk Sasah, making the ecobrick initiative highly relevant and impactful. Currently, there are three active Waste Banks operating in the village, which provided group 40 with significant support from the village government to develop and manage an inclusive and effective ecobrick program. The realization of the University’s flagship program “Maritime Resources” brought together various stakeholders, including the village government, local residents, and pioneering Waste Banks, to ensure the sustainability of this initiative. Through collaborative efforts, the ecobrick program has run smoothly, producing tangible benefits such as reducing plastic pollution, fostering creativity among community members, and promoting environmental awareness. In addition to waste management, the program integrates land use practices by planting chili and kale plants in ecobrick-based gardens to improve local food security and enhance household income. This paper highlights the importance of ecobricking as an innovative and sustainable method to manage inorganic waste and support the development of green, productive spaces for the benefit of the entire community.